'Right Taste, Wrong Place': Local Food Cultures, (Dis)identification and the Formation of Classed Identity. (December 2016) - Cappellini, Benedetta; Parsons, Elizabeth; Harman, Vicki
This article investigates how culinary taste contributes to the formation of middle class identity in a working class context in the UK. We explore practices of food consumption among a group of individuals working at a UK university located in a working class city. We find a rather limited and discrepant cosmopolitanism, in which culinary practices are evaluated in terms of those worth engaging in, and those not worth engaging in, based on their 'user friendliness' for cosmopolitan middle class dispositions. Depictions of the local food culture as lacking are also dominant, used as a negative ground against which these dispositions are hierarchically formulated. Here middle class culinary tastes seem to be driven by disengagement with the wrong sort of place and a relatively closed alignment with the 'proper' and the 'safe' rather than by any open creative individuality.